2016
DOI: 10.2139/ssrn.2778291
|View full text |Cite
|
Sign up to set email alerts
|

Eurozone Network Connectedness During Calm and Crisis: Evidence from the MTS Platform for Interdealer Trading of European Sovereign Debt

Abstract: This paper examines the connectedness of the Eurozone sovereign debt market over the period [2005][2006][2007][2008][2009][2010][2011]. By employing measures built from the variance decompositions of approximating models we are able to define weighted, directed networks that enable a deeper understanding of the relationships between the Eurozone countries. We find that connectedness in the Eurozone was very high during the calm market conditions preceding the global financial crisis but decreased dramatically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…1 Within this setting, various financial entities (i.e., assets, stock exchanges, financial institutions) are perceived as network nodes, and interdependencies across them are usually assessed by correlation measures. More recently, in the relevant literature, a set of papers that combines econometric techniques and network theory clarifies the interrelations of different entities in financial markets (e.g., Billio et al, 2012;Diebold andYilmaz, 2014, 2015;Anufriev and Panchenko, 2015;Wang et al, 2017;Stavroglou et al, 2017;Geraci and Gnabo, 2018;Hamill et al, 2019). Yet, it should be noted that calculating price returns as first-differences form of log prices can produce a stationary process, while, by using only return data, the long-run information might be lost.…”
Section: Introductionmentioning
confidence: 99%
“…1 Within this setting, various financial entities (i.e., assets, stock exchanges, financial institutions) are perceived as network nodes, and interdependencies across them are usually assessed by correlation measures. More recently, in the relevant literature, a set of papers that combines econometric techniques and network theory clarifies the interrelations of different entities in financial markets (e.g., Billio et al, 2012;Diebold andYilmaz, 2014, 2015;Anufriev and Panchenko, 2015;Wang et al, 2017;Stavroglou et al, 2017;Geraci and Gnabo, 2018;Hamill et al, 2019). Yet, it should be noted that calculating price returns as first-differences form of log prices can produce a stationary process, while, by using only return data, the long-run information might be lost.…”
Section: Introductionmentioning
confidence: 99%
“…D'Agostino and Ehrmann (2014) pointed to an overreaction of the market given the change in fundamentals and thus to a structural change in longer-term risk perception. Gross and Kok (2013), Alter and Beyer (2014), Broner et al (2014), Glover and Richards-Shubik (2014), Shoesmith (2014), Erce (2015), Li and Waterworth (2016), Lange et al (2017) discussed the relationships between private and public sector bonds, between sovereign bonds and credit derivatives, and the transmission channels between bank risk and sovereign risk. Gerlach-Kristen (2015), Blasques et al (2016), Ehrmann and Fratzscher (2017), Moessner (2018), Arakelian et al (2019) confirmed the stabilizing impact of ECB measures on bond spreads after 2012.…”
Section: Introductionmentioning
confidence: 99%
“…D'Agostino and Ehrmann ( 2014 ) pointed to an overreaction of the market given the change in fundamentals and thus to a structural change in longer-term risk perception. Gross and Kok ( 2013 ); Alter and Beyer ( 2014 ); Broner et al ( 2014 ); Glover and Richards-Shubik ( 2014 ); Shoesmith ( 2014 ); Erce ( 2015 ); Li and Waterworth ( 2016 ); Lange et al ( 2017 ) discussed the relationships between private and public sector bonds, between sovereign bonds and credit derivatives, and the transmission channels between bank risk and sovereign risk. Gerlach-Kristen ( 2015 ); Blasques et al ( 2016 ); Ehrmann and Fratzscher ( 2017 ); Moessner ( 2018 ); Arakelian et al ( 2019 ) confirmed the stabilizing impact of ECB measures on bond spreads after 2012.…”
Section: Introductionmentioning
confidence: 99%